Monetary and exchange rate policy under remittance fluctuations - Federico S. Mandelman (Federal Reserve Bank of Atlanta, 2011)
Using data for the Philippines, I develop and estimate a heterogeneous agent model to analyze the role of monetary policy in a small open economy subject to sizable remittance fluctuations. I include rule-of-thumb households with no access to financial markets and test whether remittances are countercyclical and serve as an insurance mechanism against macroeconomic shocks. When evaluating the welfare implications of alternative monetary rules, Iconsider both an anticipated large secular increase in the trend growth of remittances and random cyclical fluctuations around this trend. In a purely deterministic framework, a nominal fixed exchange rate regime avoids a rapid real appreciation and performs better for recipient households facing an increasing trend for remittances. A flexible floating regime is preferred when unanticipated shocks driving the business cycle are also part of the picture.
Keywords: F40; F41; O10; 330; remittances; small open economy; exchange rate regimes